Comparative efficacy of the modified minimally invasive “Parachute Technique” vs. the intermuscular GAP Approach in proximal humeral fracture management: a prospective study - Wei, Jia Jia; Li, Jun; Chen, Tao; Yi, Hong Chi; Zhao, Wen Tao; Tian, Tian; Wang, Jian Wei (Frontiers in Surgery, 2025)
BackgroundProximal humeral fractures (PHFs) are common in elderly individuals, often resulting from osteoporosis and falls. Surgical intervention is required for displaced fractures to restore shoulder function. This study compares the Modified Minimally Invasive Parachute Technique and the Intermuscular Gap Approach in the management of displaced PHFs.ObjectiveTo compare clinical outcomes, including surgical efficiency, complication rates, functional recovery, and radiographic healing, between the two surgical techniques.MethodsA total of 40 patients aged 60 or older with displaced two- or three-part PHFs were randomized into two groups (n = 20 per group). Primary outcomes included surgical duration, intraoperative blood loss, and postoperative drainage. Secondary outcomes included pain relief (Visual Analog Scale), shoulder function (Neer Shoulder Score), and fracture healing (Radiographic Union Scoring System, RUST).ResultsThe Parachute Technique group had significantly shorter operation times (97.25 ± 16.09 min vs. 119.75 ± 17.13 min, p < 0.001) and lower blood loss (99.00 ± 25.06 ml vs. 207.50 ± 44.47 ml, p < 0.001). Postoperative drainage was also significantly reduced in the Parachute Technique group (81.50 ± 13.48 ml vs. 119.00 ± 21.01 ml, p < 0.001). Functional recovery, assessed by the Neer Shoulder Score, was significantly better in the Parachute Technique group at 3, 6, and 12 months (p < 0.001). At 6 months, radiographic healing showed a trend towards better union in the Parachute Technique group (9.00 ± 0.73 vs. 8.60 ± 0.59, p = 0.072). Complication rates were similar between the two groups (p = 0.68).ConclusionThe Modified Minimally Invasive Parachute Technique offers superior surgical efficiency, reduced blood loss, and better functional outcomes compared to the Intermuscular Gap Approach, making it a favorable option for elderly patients with displaced PHFs.